The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/0963689720949175
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic Hematopoietic Stem Cell Transplantation for Children and Adolescents with Acute Myeloid Leukemia in Brazil: A Multicentric Retrospective Study

Abstract: The survival rates of children with high-risk acute myeloid leukemia (AML) treated with hematopoietic stem cell transplant (HSCT) range from 60% to 70% in high-income countries. The corresponding rate for Brazilian children with AML who undergo HSCT is unknown. We conducted a retrospective analysis of 114 children with AML who underwent HSCT between 2008 and 2012 at institutions participating in the Brazilian Pediatric Bone Marrow Transplant Working Group. At transplant, 38% of the children were in first compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Other studies from the same public institution where our patients came from also reported long hospitalization time and long time between diagnosis and HSCT (>12 months) for patients with low socioeconomic status (Paz et al, 2018;Pitombeira et al, 2013;Silla et al, 2009). Since the limitation in the number of hospital beds for performing HSCT in Brazil, patients with indications for transplantation and with a donor located remain on a waiting list until bed availability (Rodrigues et al, 2020). Besides the order of arrival, this list considers prioritization criteria such as age and disease type (Brazil, 2017).…”
Section: Discussionmentioning
confidence: 72%
“…Other studies from the same public institution where our patients came from also reported long hospitalization time and long time between diagnosis and HSCT (>12 months) for patients with low socioeconomic status (Paz et al, 2018;Pitombeira et al, 2013;Silla et al, 2009). Since the limitation in the number of hospital beds for performing HSCT in Brazil, patients with indications for transplantation and with a donor located remain on a waiting list until bed availability (Rodrigues et al, 2020). Besides the order of arrival, this list considers prioritization criteria such as age and disease type (Brazil, 2017).…”
Section: Discussionmentioning
confidence: 72%
“…11 In a study with Brazilian HSCT centers for children, adolescents, and young adults, OS and EFS in 4 years were 47% and 40%, respectively. 12 Brazilian outcomes of HSCT in children with AML appear to be inferior to those reported in the United States and Europe. A report by Bitan et al from the Center for International Blood and Marrow Transplant Research (CIBMTR) on 141 pediatric patients with AML who underwent the transplant in CR1 showed a 5-year PFS of 54% after myeloablative conditioning 13 .…”
mentioning
confidence: 71%
“…The results of transplants using related, unrelated (matched or partially matched, with a greater than a 8/10 HLA-match) and haploidentical donors are very similar in AML, with no significant difference between type of donor, whether in overall survival, incidence of acute or chronic graft-versus-host disease (GVHD) 12,19 . In children, bone marrow is preferable in comparison to peripheral blood (PB) as stemcell source, given the higher extensive chronic GVHD and transplant-related mortality with the use of peripheral blood stem cells 20,21 .…”
mentioning
confidence: 99%
“…A higher relapse incidence (43%) was published by de Melo Rodrigues and cols. 8 when they analyzed 114 AML patients that received MSD (49), MUD (59) and haploidentical (6) HCT. The 4-year progression-free survival (PFS) for all cohort was 40%.…”
Section: Introductionmentioning
confidence: 99%
“…Advances in immunomodulatory interventions and maintenance approaches, with tyrosine kinase inhibitors (TKI) or hypomethylating agents (HMAs), have benefit selected patients. [8][9][10][11][12][13] Pulsipher et al reported 9 , in a multicenter prospective study, risk factors and timing of relapse after allogeneic transplantation in a pediatric population diagnosed with ALL. They concluded that there is a window between day +55 and day +100 to 200 when most high-risk patients have not relapsed yet and that this population could benefit from measures to avoid relapse at that time.…”
Section: Introductionmentioning
confidence: 99%